Trikaya Parisudha-based learning management system development: Enhancing digital literacy and numeracy competencies - Suardipa, I Putu; Suharta, I Gusti Putu; Dantes, Gede Rasben; Margunayasa, I Gede; Sanjaya, Dewa Bagus (Edelweiss Applied Science and Technology, 2024)
This development research aimed to determine the validation level of the Trikaya Parisudha-based Learning Management System tool regarding digital literacy and numeracy literacy and to ascertain the practicality level of the Learning Management System tool simultaneously towards digital literacy and numeracy literacy among Primary School Education Study Program students. This research is categorized as R&D using the 4D model. The study data were collected using questionnaires. The questionnaire for validity assessment was delivered to the content and media experts. The questionnaire to evaluate the practicality of the Learning Management System was distributed to the students and lecturers of the Primary School Education Study Program at STAHN Mpu Kuturan Singaraja. Then, the data were analyzed quantitatively. This study found that the media, materials, and language of the Trikaya Parisudha-based Learning Management System developed were deemed valid by three experts. In terms of its practicality, this study confirmed that the Trikaya Parisudha-based Learning Management System media were categorized as very practical. Integrating the Trikaya Parisudha philosophy, which is deeply rooted in local cultural values, underscores the significance of embedding cultural context into educational resources, potentially improving students’ engagement and producing a more comprehensive educational experience that aligns with students’ backgrounds.